Tendon adaptation to sport-specific loading in adolescent athletes - Cassel, M.; Carlsohn, A.; Fröhlich, K.; John, M.; Riegels, N.; Mayer, F. (International Journal of Sports Medicine, 2016)
Tendon adaptation due to mechanical loading is controversially discussed. However, data concerning the development of tendon thickness in adolescent athletes is sparse. The purpose of this study was to examine possible differences in Achilles (AT) and patellar tendon (PT) thickness in adolescent athletes while considering age, gender and sport-specific loading. In 500 adolescent competitive athletes of 16 different sports and 40 recreational controls both ATs and PTs were sonographically measured. Subjects were divided into 2 age groups (< 13; = 13 years) and 6 sport type categories (ball, combat, and water sports, combined disciplines, cycling, controls). In addition, 3 risk groups (low, moderate, high) were created according to the athlete`s risk of developing tendinopathy. AT and PT thickness did not significantly differ between age groups (AT/PT:<13: 5.4±0.7 mm/3.6±0.5 mm;=13: 5.3±0.7 mm/3.6±0.5 mm). In both age groups males presented higher tendon thickness than females (p<0.001). AT thickness was highest in ball sports/cyclists and lowest in controls (p=0.002). PT thickness was greatest in water sports and lowest in controls (p=0.02). High risk athletes presented slightly higher AT thickness compared to the low risk group (p=0.03). Increased AT and PT thickness in certain sport types compared to controls supports the hypothesis of structural tendon adaptation due to sport-specific loading.